Lascivia mascherata Allegoria e travestimento in Torquato Tasso e Giovan Battista Marino - Fingerle, Maddalena (Vigilanzkulturen / Cultures of Vigilance, 2022)
How do Torquato Tasso and Giovan Battista Marino react to the vigilant and normative context between the 16th and 17th centuries? Two evasive tactics designed to safeguard lewdness and enchantment in the poems are considered, starting from the relationship the two authors had with norms and rules: allegory on the one hand, and disguise on the other. Tasso's path is evolutionary and his opinion changes according to the internalisation of laws and values that lead to a re-evaluation of his initial opinions, while Marino transgresses the rules and uses typically defensive elements - such as allegory - overturning them and inventing a concealed offensive use. In this context, the paratextual allegories of Marino's Adonis, hitherto ill-considered by critics, are thus re-evaluated, and the Tasso route is reconsidered from a perspective that sees the two authors not as victims of a censorial system, but as active participants.